1997
DOI: 10.1076/apab.105.2.158.12924
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Cells from Ovine Fetal Long Bone and Characterization of their Osteoblastic Activities duringin vitroMineralization

Abstract: Studies about bone formation and regulation are complex due to a close relationship between bone cells. Primary cell cultures allow to understand osteoblastic function. We isolated cells from the cortical metacarpal bone of 85 or 120 day-old ovine fetuses by an enzymatic method. After first passage and cell amplification, the growth medium (DMEM, ascorbic acid and fetal calf serum 10%) was replaced at confluence by a mineralization medium (MM: DMEM, ascorbic acid, beta-glycerophosphate, insulin). Alkaline phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…This enzyme is bound to the membrane of osteoblasts and functions to enhance osteogenesis by degrading pyrophosphate that inhibits crystallization at the calcification site and organic phosphate esters to increase the inorganic phosphate concentration. Therefore, ALP is considered an important marker for biomineralization and an early marker for osteoblasts or odontogenic marker genes (31). As indicated by the cytochemistry results, the ALPase activity was consistently increased in hDPC/Wnt6, with the ALP mRNA remaining at a relatively high level during the 12 days of culture.…”
Section: Discussionmentioning
confidence: 87%
“…This enzyme is bound to the membrane of osteoblasts and functions to enhance osteogenesis by degrading pyrophosphate that inhibits crystallization at the calcification site and organic phosphate esters to increase the inorganic phosphate concentration. Therefore, ALP is considered an important marker for biomineralization and an early marker for osteoblasts or odontogenic marker genes (31). As indicated by the cytochemistry results, the ALPase activity was consistently increased in hDPC/Wnt6, with the ALP mRNA remaining at a relatively high level during the 12 days of culture.…”
Section: Discussionmentioning
confidence: 87%
“…The available literature focusing on osteoblastic activities of ovine cells in vitro indicate these cells are capable of mineralisation (Collignon et al, 1997). Foetal ovine osteoblast cells stimulated post-proliferatively with ascorbic acid, β-glycerophosphate and CaCl 2 exhibited the highest ALP activity after 6 days culturing and formation of mineralisation centres from day 12.…”
Section: Ovine Cellsmentioning
confidence: 98%
“…Culture medium analysis demonstrated a rapid increase in ALP concomitant with initiation of mineralisation. Furthermore, ovine osteoblast cells produced osteocalcin in a time-dependent manner from day 6 (Collignon et al, 1997). Interestingly, a more recent study has shown that trabecular bone from ovine specimens classed as middle-aged (3-5 year old) behaved similarly to human cells isolated from the femoral condyle (donor age not known).…”
Section: Ovine Cellsmentioning
confidence: 98%
“…In the literature, however, many investigators have suggested that sheep can also be used for the study of osteoporosis. [12][13][14][15][16][17] Nevertheless, to our knowledge, very few in vitro experiments have been conducted on sheep osteoblasts [18][19] and, therefore, we undertook the present study.…”
Section: Introductionmentioning
confidence: 99%